Structure and development of the style base in Abildgaardia, Bulbostylis, and Fimbristylis (Cyperaceae, Cyperoideae, Abildgaardieae) - Reutemann Arnolfo, Andrea Guadalupe (2012)
The Abildgaardieae tribe within the family Cyperaceae comprises six or seven genera, among which Abildgaardia, Bulbostylis and Fimbristylis pose a challenge regarding their morphological delimitation. Molecular phylogenetic analyses including species of Abildgaardieae are rare, but in most of those studies, Abildgaardia and Fimbristylis appear as more closely related to each other than to the Bulbostylis genus. Duration of the style base has been one of the most widely used characters for delimiting these three genera. The style base is a persistent structure in most species of Bulbostylis and deciduous in Abildgaardia and Fimbristylis. The reasons why the style base may persist or fall off have been scarcely discussed. The assumption that abscission layers are present in the style base of all three genera and the fact that tracheids have been observed in the style base of Bulbostylis suggest that this structure might have histological complexity. In view of this, a complete ontogenetic and anatomical study of the gynoecium has been carried out for all these three genera. It turned out that the style base is histologically simple in Abildgaardia, Bulbostylis and Fimbristylis and shows similar structure and development in all three genera. The fact that the style base has a shorter duration in Abildgaardia and Fimbristylis than in Bulbostylis might be related to the lower number of sclerotised cells that make up such structures in the mature fruitof the former two genera. Abscission of the style and style base may be the result of much simpler reasons than the differentiation of an abscission layer, resulting merely from mechanical shear force effects. Differences among genera have been observed in the shape of the style base and the development of the style. The histological simplicity of the style base is consistent with the homoplastic appearance of this structure in genera that are not closely related (e.g. Rhynchospora). Because of this, while the presence of the thickened style base seems to be a synapomorphy in species of Abildgaardieae, its persistence on or detachment from the fruit might have emerged repeatedly during this clade evolution and might not be a suitable character for genera delimitation.